High step‐down interleaved buck converter with low voltage stress. Issue 12 (1st December 2015) - Esteki, Morteza; Poorali, Behzad; Adib, Ehsan; Farzanehfard, Hosein
Abstract : This study presents a four‐phase interleaved buck converter with low voltage stress and high step‐down conversion ratio. The proposed converter provides an extended duty cycle and low voltage stress for switches and diodes, in high step‐down applications. This makes it possible to use switches with lower voltage rating and thus reduce both switching and conduction losses to improve the overall efficiency. Extremely low output current ripple and continuous input current are two other advantages of the proposed converter. Also, the output current can be shared between interleaved modules without using additional current sharing control technique due to charge balance of input and blocking capacitors. All these benefits are obtained without adding any active auxiliary component or using transformers. The experimental results from a prototype of the proposed converter designed for 400–24 V, operating at 0.5 kW, verify the theoretical analysis.